Emotional and sectional conflict in the antebellum United States - Woods, Michael E. (New York, NY : Cambridge University Press, 2014)
"The sectional conflict over slavery in the United States was not only a clash between labor systems and political ideologies but also a viscerally felt part of the lives of antebellum Americans. This book contributes to the growing field of emotions history by exploring how specific emotions shaped Americans' perceptions of, and responses to, the sectional conflict in order to explain why it culminated in disunion and war. Emotions from indignation to jealousy were inextricably embedded in antebellum understandings of morality, citizenship, and political affiliation. Their arousal in the context of political debates encouraged Northerners and Southerners alike to identify with antagonistic sectional communities and to view the conflicts between them as worth fighting over. Michael E. Woods synthesizes two schools of thought on Civil War causation: the fundamentalist, which foregrounds deep-rooted economic, cultural, and political conflict, and the revisionist, which stresses contingency, individual agency, and collective passion"--
Introduction: Finding the heart of the sectional conflict -- Prologue: Slavery, sectionalism, and the affective theory of the Union -- Part I. Emotion and the Growth of Sectional Political Identities -- Free labor, slave labor, and the political economy of happiness -- Managed hearts and unmanageable slaves -- Jealousy and the sectionalization of emotional styles -- Part II. Emotion and the Mobilization of Sectional Coalitions -- Indignation and the fitful growth of mass antislavery sentiment, 1820-1856 -- Indignation and the Northern mobilization for war, 1856-1861 -- Political jealousy and Southern radicalism from nullification to secession -- Mourning and the mobilization of reluctant secessionists, 1860-1861 -- Epilogue: Reconstructing the affective theory of the Union.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Emotions -- Political aspects -- United States -- History -- 19th century; Emotions -- Social aspects -- United States -- History -- 19th century; Sectionalism (United States) -- History -- 19th century; Slavery -- Political aspects -- United States -- History -- 19th century; Slavery -- Social aspects -- United States -- History -- 19th century; Social conflict -- United States -- History -- 19th century; alueellinen identiteetti; amerikanska inbördeskriget; historia; historia; känslor; lokal anknytning; lokal identitet; orjuus; orsaker; paikallisuus; slaveri; syyt; tunteet; Yhdysvaltain sisällissota; United States -- History -- Civil War, 1861-1865 -- Causes; United States -- Politics and government -- 1815-1861.; United States -- Social conditions -- To 1865.; Förenta staterna; Yhdysvallat; 1800-luku.; 1800-talet.